CREATION AND VALIDATION OF AN INSTRUMENT ON NEOPLASTIC WOUND MANAGEMENT FOR NURSES' TRAINING - Faria, Renata Penha; Fuly, Patricia dos Santos Claro (Cogitare Enfermagem, 2023)
Objective: to create and validate the face and content of an instrument for training nurses in neoplastic wound care. Method: a methodological research study with a quantitative approach, carried out in three stages: scoping review; creation of the instrument; and face and content validation. Data collection took place between October 2021 and February 2022 in Niterói - RJ - Brazil. The Content Validation Index and Fleiss Generalized Kappa were used. Results: the final instrument consists of the following phases: definition of neoplastic wound; wound classification; staging; pain and odor rating scales; Nursing care; and management of signs and symptoms. The content was validated reaching a Content Validation Index > 0.80 and an agreement level between the judges > 75%, as established. Conclusion: validation of the instrument will contribute to reducing the gap indicated in the literature on Nursing care in relation to neoplastic wounds, in addition to its application to Nursing teaching and services.